2022
DOI: 10.1186/s12884-022-04856-z
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial analysis of cesarean section in Iran (2016–2020): exploring clustered patterns and measuring spatial interactions of available health services

Abstract: Background The lives of babies and mothers are at risk due to the uneven distribution of healthcare facilities required for emergency cesarean sections (CS). However, CS without medical indications might cause complications for mothers and babies, which is a global health problem. Identifying spatiotemporal variations of CS rates in each geographical area could provide helpful information to understand the status of using CS services. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…This may be due to referrals from their PCPs (Geissler et al, 2021;Victoor et al, 2012). Additionally, a previous study (Mohammadi et al, 2022) identified the interaction between travel distance and hospital capacity as a crucial factor in increasing the spatial gravity for emergency Cesarean section. These findings suggest that the spatial factor, when it becomes significant, may interact with other non-spatial factors.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to referrals from their PCPs (Geissler et al, 2021;Victoor et al, 2012). Additionally, a previous study (Mohammadi et al, 2022) identified the interaction between travel distance and hospital capacity as a crucial factor in increasing the spatial gravity for emergency Cesarean section. These findings suggest that the spatial factor, when it becomes significant, may interact with other non-spatial factors.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical, spatio-temporal scans and spatial interaction analysis were used in it. The evaluation was carried out using geographic information systems [ 43 ].…”
Section: Methodsmentioning
confidence: 99%